Tri‐orthogonal polarization diversity for 5G networks. Issue 7 (3rd May 2016) - Lawrence, Nicholas P.; Hansen, Hedley; Abbott, Derek
Abstract: Millimetre‐waves offer the possibility of wide bandwidth and consequently high‐data rate for wireless communications. For both uni‐polarised and dual‐polarised systems, signals sent over a link may suffer severe degradation because of antenna misalignment. Orientation robustness may be enhanced by the use of mutual orthogonality in three dimensions. Multiple‐input multiple‐output polarisation diversity offers a way of improving signal reception without the limitations associated with spatial diversity. Scattering effects often assist propagation through multipath. However, high‐path loss is often considered to limit millimetre‐wave propagation, thereby reducing any reception enhancement through scattering. We show that the inclusion of a third orthogonal dipole at a frequency of commercial interest provides antenna orientation robustness in this setting, as well as improved performance in a rich scattering environment, by means of a Ricean fading channel model. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Through a fundamental physical approach to tri‐orthogonal antenna operation at a frequency designated to 5G networks, we show that the inclusion of a third orthogonal polarization provides orientation robustness and an overall increase in capacity performance over conventional circular polarization techniques.